2014
DOI: 10.1097/shk.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remote Ischemic Preconditioning and Myocardial Ischemia on MicroRNA-1 Expression in the Rat Heart In Vivo

Abstract: Remote ischemic preconditioning (RIPC) is an easily applicable method for protecting the heart against a subsequent ischemia and reperfusion (I/R) injury. However, the exact molecular mechanisms underlying RIPC are unknown. We examined the involvement of microRNAs (miRNAs) and in particular the expression of miRNA-1 (miR-1) in RIPC and myocardial ischemia. Remote ischemic preconditioning was conducted by four cycles of 5-min bilateral hind-limb ischemia in male Wistar rats. Cardiac ischemia was induced by liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Importantly, AMO-1 transfection markedly suppressed the inhibitory effect of miR-1 on p-CREB (P < 0.05). Taken together, these data indicate that BDNF is a potential target of miR-1, which is consistent with the findings of previous studies (Brandenburger et al, 2014;Varendi et al, 2014) .…”
Section: Impairment Of Cognition In Mir-1 Tg Micesupporting
confidence: 93%
“…Importantly, AMO-1 transfection markedly suppressed the inhibitory effect of miR-1 on p-CREB (P < 0.05). Taken together, these data indicate that BDNF is a potential target of miR-1, which is consistent with the findings of previous studies (Brandenburger et al, 2014;Varendi et al, 2014) .…”
Section: Impairment Of Cognition In Mir-1 Tg Micesupporting
confidence: 93%
“…As a complex organ with various cell types, cerebral tissues have different cellular components and synaptic connections at (20). In cerebral tissues, cells of different types have individual expression profiles (44). In the present study, we also demonstrated that SIRT1 exerted neuroprotective effects by increasing microRNA-22 expression in rats with CIRI.…”
Section: Discussionsupporting
confidence: 69%
“…Secondly, it has been reported that miR-1 is dysregulated in mouse DRG in different pain states (Kusuda et al, 2011). Thirdly, miR-1 negatively modulates Bdnf gene expression (Brandenburger et al, 2014;Varendi et al, 2014) and inhibits expression of the neuropathic pain-associated proteins Hsp60 and Cx43 (Pan et al, 2012;Shan et al, 2010;Yang et al, 2007). To regulate specific A C C E P T E D M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 98%
“…The protein is critically involved in pathological nociceptive processes such as neuropathic pain (Coull et al, 2005). It has been demonstrated previously that microRNA-1 (miR-1) negatively regulates BDNF expression by directly targeting the 3` untranslated region (UTR) of Bdnf mRNA (Brandenburger et al, 2014;Varendi et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%